Experimental Confirmation of Low Surface Energy in LiCoO2 and Implications for Lithium Battery Electrodes1. Issue 46 (23rd September 2013) - Maram, Pardha S.; Costa, Gustavo C. C.; Navrotsky, Alexandra
<x xml:space="preserve">Abstract</x> Water adsorption on the surface of LiCoO2 nanoparticles was investigated. As the water coverage increases the adsorption enthalpy decreases reaching the enthalpy of water condensation (−44 kJ mol−1). The experimentally observed average surface energy corresponding to all facets agree well with those reported from DFT calculations. The observed low surface energy is attributed to the surface Co3+ spin transition in nanophase LiCoO2.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>